Image of tsar Peter in the medieval Bulgarian sources - Leszka, Mirosław (Balcanica Posnaniensia. Acta et studia, 2018)
The article is devoted to image of tsar Peter in medieval Bulgarian sources (10th-14th c.). Bulgarian sources did not give modern historians to chance of researching of the Peter’s ruling. They could be useful in studying the cult of tsar Peter and memory about him.